REPORTS AND AWARENESS OF RESTAURANT TAXPAYERS AND SOCIALIZATION OF THE SYSTEM TO INCREASE PAD IN BANJARBARU CITY - Edy Joko Soewanto (JURNAL KINDAI, 2021)
Abstract: Reports and Awareness of Restaurant Taxpayers and Socialization of the System to Increase PAD in Banjarbaru City, under the guidance of Mr. H. Nurus Sjamsi and Mr. H. Ihil S Baron, as supervisors I and II.This research was conducted with the aim of analyzing the simultaneous effect of reporting, taxpayer awareness and system socialization on the PAD of Banjarbaru City; analyze the partial effect of reporting, awareness of taxpayers and the socialization of the system to PAD Kota Banjarbaru; and analyze the reporting variables, awareness of taxpayers and socialization that have a dominant effect on PAD of Banjarbaru City.Analysis of the data used in this study is quantitative descriptive with a sample of 80 taxpayer respondents, using multiple linear regression test data analysis.The results of the study concluded that the reporting, awareness of taxpayers and simultaneous socialization of the system significantly influence the original income of the Banjarbaru City. Partially reporting, awareness of taxpayers and socialization have a significant effect on the original income of the Banjarbaru City. The variable that has dominant influence on the original income of the Banjarbaru City is socialization, because the significant value is greater than the other variables.Keywords: Reporting, Taxpayer Awareness, System Socialization, PAD Banjarbaru CityAbstrak: Laporan Dan Kesadaran Wajib Pajak Restoran Serta Sosialisasi Sistem Untuk Meningkatkan PAD Kota Banjarbaru, dibawah bimbingan Bapak H. Nurus Sjamsi dan Bapak H. Ihil S Baron, selaku dosen pembimbing I dan II.Penelitian ini dilaksanakan dengan tujuan untuk menganalisis pengaruh simultan dari pelaporan, kesadaran wajib pajak dan sosialisasi sistem terhadap PAD Kota Banjarbaru; menganilisis pengaruh parsial dari pelaporan, kesadaran wajib pajak dan sosialisasi sistem terhadap PAD Kota Banjarbaru; dan menganalisis dari variabel pelaporan, kesadaran wajib pajak dan sosialisasi yang berpengaruh dominan terhadap PAD Kota Banjarbaru.Analisis data yang digunakan dalam penelitian ini adalah deskriptif kuantitatif dengan sampel sebanyak 80 responden wajib pajak, menggunakan analisis data uji regresi linier berganda.Hasil penelitian menyimpulkan bahwa pelaporan, kesadaran wajib pajak dan sosialisasi sistem secara simultan berpengaruh signifikan terhadap pendapatan asli daerah Kota Banjarbaru. Secara parsial pelaporan, kesadaran wajib pajak dan sosialisasi berpengaruh signifikan terhadap pendapatan asli daerah Kota Banjarbaru. Variabel yang berpengaruh dominan terhadap pendapatan asli daerah Kota Banjarbaru adalah sosialisasi, karena nilai signifikan lebih besar pengaruhnya dibanding dengan variabel yang lain.Kata kunci: Pelaporan, Kesadaran Wajib Pajak, Sosialisasi Sistem, PAD Kota Banjarbaru